ANALISIS BAURAN PROMOSI PADA PT.ANUGRAH PARAHYANGAN JAYA - Sofyan, Yayan (2018)
Marketing is a major force in business and society that began and ended the needs of consumers. The concept of marketing is a whole system of business activities to plan, determine pricing, promoting and distributing goods or services that can satisfy consumer needs, analysis of the results of the implementation of the strategy is important for the Promotion Mix done to see how far the influence of these promotion strategies in increasing the value company's sales. The results of this analysis will be useful as guidelines for the management of companies, especially companies Ciroyom market developers to take steps appropriate policies and targeted. The data analysis process to organize and sort the data into patterns, categories and units so that the basic outline can be found in the theme and can be formulated as a working hypothesis based on the data, the authors analyzed the data using the method of calculating the average (mean), mode, and median Implementation of the Promotion Mix PT.Anugrah Parahyangan Plaza is on the radio ads, billboard installation in strategic places, distributed brochures places crowded with ads consumers are expected to know more about PT.Anugrah Parahyangan Jaya so that companies can reap the results of purpose of the advertising that is increasing demand for early, developing the options on the company and the last to convince buyers of the products offered by PT.Anugrah Parahyangan Jaya can be enjoyed by consumers Sales promotions conducted in PT.Anugrah Parahyangan Jaya using time rebate form discount if consumers buy a kiosk or shop at a specific time and is proven effective to stimulate sales in a short time and in the long term the company can attract new customers, sales personnel in PT . Anugrah Jaya Parahyangan by direct communication between the SPG to the consumer, usually PT.Anugrah Parahyangan Jaya following property trade show organized by Event Orgazer resulting in direct contacts between the SPG PT.Anugrah Parahyangan Jaya with consumers and this usually occurs when the consumer transaction fits with the bid offered by the company